HUBUNGAN DURASI DUDUK DAN POSTUR KERJA TERHADAP KELUHAN LOW BACK PAIN PADA KARYAWAN BANK KB BUKOPIN TAHUN 2022 - Ratu Sheila Annamyra (2022)
Low Back Pain is one of the most serious diseases and injuries, with a higher average DALY (Disability-Adjusted Life Years) than HIV, traffic accidents, tuberculosis, lung cancer, chronic obstructive pulmonary disease and complications of premature birth. In the world, LBP disease every year touches 15-45%. The purpose of this study was to analyze the relationship between sitting duration and work posture as well as individual factors such as age, years of service, body mass index, and exercise habits to complaints of low back pain to Bank Kb Bukopin employees. This research method is quantitative analytic with a cross sectional study design. The sampling technique used is total sampling with 62 respondent. The results of this study indicate that most of the respondents are 35 years old (78.1%), new work period < 10 years (68.8%), body mass index is not at risk 25 (60.6%), exercise habits < 3 times a week (78.8%), sitting duration 4 hours (90.0%), and unacceptable work posture > 2 (82.2%). Based on the results of statistical analysis, it can be concluded that there is a significant relationship between body mass index and sitting duration with complaints of low back pain. Therefore, it is necessary to stretch in between work, living a healthy lifestyle, and get enough rest.